Autoimmune urticaria in Rumah Sakit Umum Pusat Dr. Moh. Hoesin Palembang - Thaha, M. Athuf (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: About 30% patients with chronic idiopathic urticaria (CIU)have circulating histamine-releasing autoantibodies against the a-subunit of high affinity IgEreceptor (FceRla),or IgE.This subgroup of patients has a disorder commonly referred as autoimmune urticaria. Objectives: This study was conducted to reveal the autoimmune urticariacases in Indonesian patients Methods: The autologous serum skin test (ASST)and histamine release assay (HRA)were conducted on 79 patients with CIU (53 females and 26 males). Patients with predominant physical urticaria and urticarial vasculitis were excluded from the study. Results: Seventeen patients had both positive autologous serum skin test and histamine release assay confirmative of autoimmune urticaria. Conclusion:CombinedpositiveASSTand HRAwere seen in 21.5% of CIUpatients, indicatingautoimmune urticaria. Key words: chronic idiopathic urticaria - anti-FceRla histamine-releasing autoantibodies -autoimmune urticaria - autologous serum skin test, histamine release assay.